1983
DOI: 10.1111/j.1365-2621.1983.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of fish fillets and minced fish by both sensory and instrumental methods

Abstract: Summary In an attempt to establish objective criteria for texture analysis as an effective substitute for organoleptic procedures, correlation between the results obtained by a panel of tasters and physical and chemical analyses of texture was determined. In addition, regression equations relating instrumental and sensory methods were applied to predict sensory data from those obtained during instru mental analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…Sigurgisladottir et al (1999) found the shear force method based on cutting with a knife blade more sensitive than the puncture method and more discriminatory when the determining textural properties of different locations. Finally, Borderias, Lamua, and Tejada (1983) reported the compression method to be quick, accurate and reliable for analysing raw fish.…”
Section: Discussionmentioning
confidence: 98%
“…Sigurgisladottir et al (1999) found the shear force method based on cutting with a knife blade more sensitive than the puncture method and more discriminatory when the determining textural properties of different locations. Finally, Borderias, Lamua, and Tejada (1983) reported the compression method to be quick, accurate and reliable for analysing raw fish.…”
Section: Discussionmentioning
confidence: 98%
“…Emulsion stability is also dependent of these conditions (Gordon & Barbut, 1992). Functionality of meat protein is reported being species-specific (Jimé-nez-Colmenero & Borderías, 1983) as well as depending on originating in the smooth or striated muscle (Borderías, Lamua, & Tejada, 1983;Whiting, 1988). Differences seem to be related to polymorphism; in the case of light meromyosin its molecular weight is both, species-and muscle-specific (Smith, 1988).…”
Section: Introductionmentioning
confidence: 95%
“…Instrumental texture analysis used for terrestrial muscle foods lacks repeatability when used with fish fillets (Borderias and others 1983). In shear test using 5‐blade Allo‐Kramer (AK) attachment, the myotome layers tend to slide away by the applied force and resistance to the applied force is accounted for by shearing a bulk of muscle fiber collected within the shear cell area (Figure 1).…”
Section: Introductionmentioning
confidence: 99%